A 20‐Year Study of Melt Processes Over Larsen C Ice Shelf Using a High‐Resolution Regional Atmospheric Model: 1. Model Configuration and Validation. Issue 8 (26th April 2022) - Gilbert, Ella; Orr, Andrew; King, John C.; Renfrew, Ian A.; Lachlan‐Cope, Thomas
Abstract: Following collapses of the neighboring Larsen A and B ice shelves, Larsen C has become a focus of increased attention. Determining how the prevailing meteorological conditions influence its surface melt regime is of paramount importance for understanding the dominant processes causing melt and ultimately for predicting its future. To this end, a new, high‐resolution (4 km grid spacing) Met Office Unified Model (MetUM) hindcast of atmospheric conditions and surface melt processes over the central Antarctic Peninsula is introduced. The hindcast is capable of simulating observed near‐surface meteorology and surface melt conditions over Larsen C. In contrast with previous model simulations, the MetUM captures the observed east‐west gradient in surface melting associated with foehn winds, as well as the interannual variability in melt shown in previous observational studies. As exemplars, we focus on two case studies—the months preceding the collapse of the Larsen B ice shelf in March 2002 and the high foehn, high melt period of March‐May 2016—to test the hindcast's ability to reproduce the atmospheric effects that contributed to considerable melting during those periods. The results suggest that the MetUM hindcast is a useful tool with which to explore the dominant causes of surface melting on Larsen C. Plain Language Summary: Scientists are concerned about floating ice shelves on the Antarctic Peninsula because several shelves have collapsed there in recent decades, due partly to melting at the surface. However, our understanding of what causes these ice shelves to melt is limited by the lack of observations in the region, and so numerical models are an extremely useful tool to explore melt processes. This study showcases a new high‐quality model data set that is able to capture the major patterns of surface melting and atmospheric conditions over ice shelves on the Antarctic Peninsula. It represents an improvement on previous studies and can therefore be used to examine melt and meteorology on ice shelves like Larsen C. The ability of the hindcast to capture these processes is illustrated via two case studies—the period just before the collapse of the Larsen B ice shelf in March 2002, and a period in March‐May 2016 when exceptionally high melt and intense foehn winds were observed on the Larsen C ice shelf. Simulations of reasonable accuracy suggest that the hindcast is suitable for exploring the causes of ice shelf surface melting in the region. Key Points: We present a new high‐resolution, multidecadal hindcast of atmospheric conditions, and surface melt processes over the Larsen C ice shelf The MetUM hindcast captures the expected location, frequency, and interannual variability of foehn events on Larsen C The hindcast captures the foehn‐induced distribution and interannual variability of surface melt patterns on Larsen C